Adherence and persistence among patients with type 2 diabetes initiating dulaglutide compared with semaglutide and exenatide BCise: 6‐month follow‐up from US real‐world data. Issue 1 (11th October 2020) - Mody, Reema; Yu, Maria; Nepal, Bal; Konig, Manige; Grabner, Michael
Abstract: Aim: To compare 6‐month adherence, persistence and treatment patterns among patients initiating once‐weekly glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs), dulaglutide versus semaglutide, and dulaglutide versus exenatide BCise, using claims from the HealthCore Integrated Research Database. Materials and methods: Patients aged ≥18 years, with type 2 diabetes, ≥1 claim for dulaglutide, semaglutide or exenatide BCise during the index period February 2018 to December 2018 (index date = earliest GLP‐1RA fill date), no claim for GLP‐1RAs in the 6‐month pre‐index period, and continuous enrolment 6 months pre‐ and post‐index were included. Dulaglutide users were propensity‐matched 1:1 to semaglutide users (3852 pairs) or exenatide BCise users (1879 pairs). The proportions of adherent (proportion of days covered ≥80%) patients were compared using chi‐squared tests. Persistence, measured as days to discontinuation, was analysed using a Cox regression model. Results: Matched cohorts (dulaglutide:semaglutide and dulagutide:exenatide BCise) were balanced in baseline characteristics and the mean age was 54 and 55 years, respectively, with approximately 51% and 49% women, respectively. At 6 months, significantly more dulaglutide users were adherent than semaglutide (59.7% vs. 42.7%; P <0.0001) or exenatide BCise users (58.1% vs. 40.3%; P <0.0001). Cox regression showed that dulaglutide users were less likely to discontinue therapy than semaglutide (hazard ratio [HR] 0.71, 95% confidence interval [CI] 0.66, 0.76) or exenatide BCise users (HR 0.59, 95% CI 0.53, 0.65; P <0.0001, both). Conclusion: At 6‐month follow‐up, a higher proportion of patients initiating dulaglutide were adherent to and persistent with their treatment, compared to matched patients initiating either semaglutide or exenatide BCise.